FAKTOR DOMINAN YANG MEMPENGARUHI PENURUNAN NAFSU MAKAN PADA PASIEN GASTRITIS - Rabiah Marhabang; Kastubi .; Bambang Hari Subagyo (JURNAL PENELITIAN KESEHATAN, 2014)
Gastritis is inflammation of the gastric mucosa and can be caused by irritation and infection(Wijoyo, 2009). Decreased appetite often occurs during an attack of gastritis. Many factors cause adecrease in appetite, such as nausea, anxiety, and abdominal pain. This research is a kind of analyticalresearch korellasional design that aims to analyze the dominant factor affecting the decrease in appetite ingastritis patients in Puskesmas Sugio Lamongan district . The study population was all patients withgastritis in Puskesmas Sugio. While the sample is partially and the population, were selected by simplerandom sampling as many as 34 people. Independent variable is a factor: nausea, anxiety, and abdominalpain. While the dependent variable is a decrease in appetite. Hash was analyzed using multivariate linearregression statistical test values obtained Standardized Coefficients and anxious to have the highest value,which is -0.145. Therefore concluded that the anxiety factor is the dominant factor affecting the decreasein appetite in patients with gastritis in Puskesmas Sugio Lamongan. Suggested: the health professionals if it finds gastritis patients, it should be noted the level of anxiety, so that the patient does not experience a decrease in appetite. Keywords: dominant factor, appetite, gastritis.